Keeping Up With The Joneses: Assessing Phishing Susceptibility in an Email Task. (September 2013) - Hong, Kyung Wha; Kelley, Christopher M.; Tembe, Rucha; Murphy-Hill, Emerson; Mayhorn, Christopher B.
Most prior research on preventing phishing attacks focuses on technology to identify and prevent the delivery of phishing emails. The current study supports an ongoing effort to develop a user-profile that predicts when phishing attacks will be successful. We sought to identify the behavioral, cognitive and perceptual attributes that make some individuals more vulnerable to phishing attack than others. Fifty-three participants responded to a number of self-report measures ( e.g., dispositional trust) and completed the 'Bob Jones' email task that was designed to empirically evaluate phishing susceptibility. Over 92% of participants were to some extent vulnerable to phishing attacks. Additionally, individual differences in gender, trust, and personality were associated with phishing vulnerability. Application and implications for future research are discussed.